Analisis Framing Model Robert N Entman Tentang Penerapan Kembali Tilang Manual Jakarta di Kompas.com dan Tempo.Com - Feby Jolanda Olivia; Hendra Setiawan (Peneliti.net, 2023)
Framing is a the viewpoint that journalists or media use in writing and presenting the news. One of the current media outlets is the re-application of the manual traffic law enforcement in Jakarta. The analysis aims to analyze news framing in the media Kompas.com and Tempo. Com uses the four-part news element Robert N. Entman model. This analysis also aims to know how a medium in shaping and presenting a message to the public. The study used qualitative research with descriptive methods and was carried out using documentation techniques. The documentation technique is carried out by taking news screenshots on digital media Kompas.com and Tempo.co. In the results of this study, it was found that Kompas.com in packing the news presents facts in the establishment of people's minds as an urgency or importance. Violations committed by the community are a big reason why this manual traffic law enforcement is reinstated. Tempo.co in packing the news denotes emphasizes on the title